ANALISIS PERBANDINGAN TOTAL DISSOLVED SOLID (TDS) DI PERAIRAN UTARA KABUPATEN SAMPANG MENGGUNAKAN DATA AQUAMODIS - Aly Shobry Syaifullah; Siti Zainab (LPPM Universitas Abdurrab, 2025)
Sampang Regency is located in East Java Province which is geographically located between 113°08' - 113°39' East Longitude and 6°05' - 7°13' South Latitude. There are 3 sub-districts on the north coast of Sampang Regency, namely Sokoban, Banyuates, and Ketapang which have the potential for fish markets, tourism, and so on. One of the uses of remote sensing can help to know the quality of waters in an area so that it is able to provide information related to marine potential. This study aims to determine the empirical algorithm, value and distribution mapping of Total Dissolved Solid (TDS). The results of the t-test processing obtained a result of -0.00024 which means that there is no significant difference between the value of the field TDS andthe point of collection at TDS in the 2023 image And in the Anova test, the results were obtained on rows shows F count = 1.336676, meaning that there is no significant difference between the value of T, D, S, field and the point of pickup in TDS in the 2019 to 2023 image and columns show F count = = 18.75428 greater than F crit = 2.310225 meaning there is a difference between TDS field dengan TDS 2019 imagery to 2023. The distribution of Total Dissolved Solid (TDS) concentrations in the northern waters of Sampang Regency has a minimum value range of 25 mg / l to a maximum of 39 mg/l.